STRATEGI KOMUNIKASI PETUGAS BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN CABANG PADANG MENUJU PELAYANAN PRIMA - Dewi Faradilla,; Elva Ronaning Roem,; Sarmiati, (Mediakita, 2020)
One of the basic human needs that is guaranteed by the government of a country is health insurance. In Indonesia, the state business entity designated to provide health services for all Indonesians is the Health Social Security Administration (BPJS) which has spread throughout the regions. In providing services to participants, a communication strategy is needed that is in accordance with the needs of the participants. This study will provide a description of the communication strategies used by BPJS Kesehatan Padang Branch in providing public services to JKN-KIS participants. This study used a descriptive qualitative method with data collection using interview methods and documentation sources. The results of this study show that the services provided are in accordance with Law Number 25 of 2009 concerning Public Services which is then developed through trainings provided to service officers (frontliners) who directly face JKN-KIS participants so that the expected services are in accordance with participant needs. The public services provided are also supported by appropriate facilities and infrastructure, both verbal and non-verbal communication facilities.